Cultural attitudes toward sport psychology: insights from Italian athletes and coaches - Simonti, Gabriele; Kamphoff, Cindra; McAlarnen, Michelle; Kratimenos, Panagiotis; Quartiroli, Alessandro (Frontiers in Psychology, 2025)
IntroductionSport psychology (SP) examines the mental factors that influence athletic performance and well-being. Although the field has experienced substantial global growth over the past decade, much of the existing literature remains rooted in AngloSaxon cultural contexts, raising questions about its applicability in other cultural contexts.MethodsThis study explored context-specific perceptions of SP by examining the attitudes of two key sport stakeholders—Italian athletes (n = 298; 50.17%) and coaches (n = 296; 49.83%). Participants (male = 324; 54.45%; female = 270; 45.55%) represented both individual and team sports, across elite and non-elite competitive levels. An online survey assessed participants’ perceptions and attitudes toward SP services and professionals. Using Brislin’s back-translation method, we adapted the SPA-R and SPARC-2 into Italian.ResultsConfirmatory factor analysis confirmed the internal structure of the instruments in the Italian sample. We then examined differences in attitudes by stakeholder role, gender, age, and competitive level. Overall, both athletes and coaches reported low levels of stigma and high confidence in SP and its services. However, significant differences were observed across demographic groupsDiscussionThis study provides a culturally grounded snapshot of the current sport psychology landscape in Italy, highlighting context-specific attitudes and offering valuable insights for enhancing the cultural relevance of SP services and advancing global understanding of the field.